1991
DOI: 10.1111/j.1365-2125.1991.tb05590.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction between propranolol and the HMG‐CoA reductase inhibitors pravastatin and lovastatin.

Abstract: 1 Single oral 20 mg doses of the HMG-CoA reductase inhibitors pravastatin and lovastatin, with and without concomitant propranolol (40 mg twice daily), were administered to 16 healthy male subjects participating in a randomized, four-way crossover study. 2 Serum concentrations of total and active inhibitors were measured by bioassay and concentrations of pravastatin, two pravastatin metabolites and lovastatin acid were measured by gas chromatography/mass spectrometry. 3 Coadministration of propranolol with pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…study was reported in the literature 2. Eight single oral dose PKs with different doses were reported in the literature: 0.0372 mg,10 19.2 mg,2 20 mg,11, 12 40 mg,13, 14, 15 and 60 mg 16. Clinical studies used for the PBPK model development: i.v.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…study was reported in the literature 2. Eight single oral dose PKs with different doses were reported in the literature: 0.0372 mg,10 19.2 mg,2 20 mg,11, 12 40 mg,13, 14, 15 and 60 mg 16. Clinical studies used for the PBPK model development: i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies used for the PBPK model development: i.v. dose of 9.4 mg 2 and oral dose of 40 mg13, 14, 15; clinical studies used for the PBPK model verification: oral dose of 0.0372 mg,10 19.2 mg,2 20 mg,11, 12 and 60 mg 16…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were small (23% and 26%) increases in the mean AUC and Cmax values of pravastatin during co-administration of digoxin, the values of these parameters were within the ranges reported following single or multiple therapeutic doses of pravastatin [2][3][4]9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of pravastatin appear linear for AUC and Cmax with respect to dose [2]. The elimination half-life of pravastatin is about 1.5 h; it is 50% to 60% bound to plasma proteins and is eliminated equally by renal and non-renal routes [3][4][5]. Pravastatin is detected in plasma as the parent compound together with two of its much less active metabolites, SQ 31,906 (the 3ot-hydroxy isomer) and SQ 31,945 (the tri-hydroxy metabolite) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%